IMPLEMENTASI KURIKULUM MERDEKA DI PAUD BINA KARYA BANDAR MASILAM TERHADAP TANGGUNG JAWAB DAN DISIPLIN ANAK - Nurliyah Nasution; Rani Endah Lestari; Rahma Handayani; Sri Ratna Dewi (Jurnal Al Athfaal, 2023)
The purpose of this study was to determine the effectiveness of the current independent curriculum in developing children's sense of responsibility and discipline. This research was conducted in PAUD located in Bandar Masilam Sub-district. The research was conducted in the first semester, which includes planning research activities, implementing research activities, and collecting data. The population of this study was all children with similar characteristics who attended PAUD BINA KARYA in Bandar Masilam sub-district. The study found that children who used the independent curriculum were more responsible and disciplined than those who did not. This is because the independent curriculum has made students familiar with the profile of Pancasila so that it is easier to apply. The Implimintation of Merdeka Curriculum in Early Childhood Education (ECED) is an Effort to build responsibility and discipline in early childhood. This curriculum approach prioritizes moare flexsible learning, according to the interests and potential of each child. With a focus on personal interacktion and enganging activities, children are encouraged to develop a sense of responsibility for their own learning, and have the freedom to choose activities that suit their interests. Through more active and engaged learning experiences, Merdeka curriculum builds discipline by following children’s individual development and interests, encoruraging intrinsic motivation to learn, and respecting axisting rules. Research at BINA KARYA PAUD revealed that the implementation of Merdeka Curriculum has gone through strict standards. Can affect the planning, implementation and evaluation stages and can affect children's responsibility and discipline. This foundation is the basis for implementing Merdeka Curriculum in ECD to build responsibility and discipline in children from an early age, integrating these values into their learning experiences.